2015
DOI: 10.1186/s12868-015-0190-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of preferential A- and C-fibre blocks and T-type calcium channel antagonist on detection of low-force monofilaments in healthy human participants

Abstract: BackgroundA myriad of studies have argued that tactile sensibility is underpinned exclusively by large myelinated mechanoreceptors. However, the functional significance of their slow-conducting counterparts, termed C-low threshold mechanoreceptors (C-LTMRs), remains largely unexplored. We recently showed the emergence of brush- and vibration-evoked allodynia in human hairy and glabrous skin during background muscle pain. The allodynia persisted following the preferential blockade of myelinated fibres but was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Recently, it was shown in mice that VGLUT3 (vesicular glutamate transporter)-expressing C-LTMRs release TAFA4 protein when activated, and intrathecal administration of TAFA4 reverses hyperalgesia. Conversely, in mice, low-threshold T-type calcium channel, Cav3.2, is a selective marker for small diameter mechanoreceptors expressing VGLUT3/TAFA4/tyrosine hydroxylase and, more importantly, a conditional knockout of Cav3.2 on C-LTMRs resulted in the attenuation of mechanical and cold allodyniaan observation confirmed in humans by the use of a peripheral T-channel antagonist (Francois et al, 2015;Nagi et al, 2015;Samour et al, 2015). Likewise, GINIP, a Ga1-interacting protein, expressed on nonpeptidergic C fibres (including C-LTMRs) has been shown to modulate the GABAergic inhibition of nociceptive transmission at the spinal level (Gaillard et al, 2014).…”
Section: Pain Reduction By Touchmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, it was shown in mice that VGLUT3 (vesicular glutamate transporter)-expressing C-LTMRs release TAFA4 protein when activated, and intrathecal administration of TAFA4 reverses hyperalgesia. Conversely, in mice, low-threshold T-type calcium channel, Cav3.2, is a selective marker for small diameter mechanoreceptors expressing VGLUT3/TAFA4/tyrosine hydroxylase and, more importantly, a conditional knockout of Cav3.2 on C-LTMRs resulted in the attenuation of mechanical and cold allodyniaan observation confirmed in humans by the use of a peripheral T-channel antagonist (Francois et al, 2015;Nagi et al, 2015;Samour et al, 2015). Likewise, GINIP, a Ga1-interacting protein, expressed on nonpeptidergic C fibres (including C-LTMRs) has been shown to modulate the GABAergic inhibition of nociceptive transmission at the spinal level (Gaillard et al, 2014).…”
Section: Pain Reduction By Touchmentioning
confidence: 94%
“…In the current study, vibration frequency and stroking velocity parameters were set based on previous electrophysiological data (Wessberg et al, 2003;L€ oken et al, 2009;Ackerley et al, 2014) on the responsiveness of CT afferents defining them as being optimal or sub-optimal. A recent study showed that skin indentation with monofilament contacts, a stimulus which activates both Ab and CT afferents (Cole et al, 2006;Nagi et al, 2015), produces analgesia when delivered simultaneously with infrared laser heat (Mancini et al, 2014). Interestingly, other studies have argued an intensity-dependent effect of stroking, as it tapered off with an increase in laser strength from a barely detectable condition to pain threshold and above (Kakigi and Shibasaki, 1992;Nahra and Plaghki, 2003).…”
Section: Pain Reduction By Touchmentioning
confidence: 99%
“…It is worth noting that the C cold fibres and C-LTMRs are both responsive to skin cooling, and while the former have been found to be mechanically insensitive, the latter have been implicated in ‘crude’ detection of low-force punctate mechanical stimuli [18, 28]. The residual incidence of WP following compression blockade—when the cooled stimulus was presented second (66.7 ± 5.5%)—suggests that the C-LTMRs can contribute to tactile–thermal interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent experimental sitting, the myelinated fibres of the ulnar nerve were preferentially blocked using compression of the ulnar nerve by placing a small metal slab just proximal to the medial epicondyle of humerus [16, 18]. This was successfully achieved in 9 of the 11 subjects—the block failed to take effect in one subject and another failed to show up for the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Pan T-type blockers that block burst-firing in both VB [18] and TRN [31] neurons have been shown to suppress seizures in animal models of absence epilepsy [31, 58], prevent seizure kindling in a model of complex-partial seizures [59], and suppress tonic-clonic seizures [60]. In terms of pain signalling, pan T-type antagonists have shown efficacy in reducing pain sensation in both animal models [54, 61–63] and humans [64, 65]. T-type calcium currents underlying burst-firing and slow oscillations in the thalamocortical system have been extensively linked to non-REM sleep [6].…”
Section: Discussionmentioning
confidence: 99%